An ethics-based systems approach to indicators of sustainable development. (1st January 2000) - Peet, John; Bossel, Hartmut
A society that wishes to implement policy for sustainable development is faced with the need to identify both the desired direction of any change that is needed and the criteria by which it will know whether its policy has succeeded. These requirements are usually seen as essentially technical in nature. We argue that the ethical framework that a society uses to govern its continuing relationship with all other life on Earth will act as a filter for the indicators that are selected to implement its social control functions. Choice of the ethical framework is therefore primary. This paper postulates the moral imperative of sustainability, and suggests an ethical statement to rationalise social actions and act as a filter for appropriate indicators. Bossel's general systems approach and the use of his basic orientors of system viability are then described, as a structural framework for specification and definition of indicators of system sustainablity. The approach is illustrated by applying it to the New Zealand economy-environment-society system.